Viral and host determinants of the impact of human cytomegalovirus in immunocompromised adults from Australia and Indonesia - Waters, Shelley Anne (Curtin University, 2022)
This thesis explores a virus that is carried by about 80% of the world’s population called cytomegalovirus. Cytomegalovirus can cause disease in people whose immune systems are dysfunctional. The thesis focuses on the cytomegalovirus itself and utilises deep sequencing technologies to identify a range a variants. The genetic variants are then linked with immune responses to HCMV and markers of cardiovascular diseases in renal transplant recipients, people living with HIV and neonates.